Pengaruh Lingkungan Sekolah terhadap Perkembangan Karakter Siswa Sekolah Dasar : Tinjauan Literatur (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This research aims to examine the influence of the school environment on the character development of elementary school students through the Systematic Literature Review (SLR) approach. The main focus is on the role of teachers and the condition of the school environment as important factors in the formation of students' character, especially amid the challenges of technological development and digitalization. Five relevant articles from 2021-2025 were systematically analyzed to obtain a comprehensive overview. The study findings show that a safe, inclusive and supportive school environment, as well as teachers who serve as positive role models, are helpful in creating values such as discipline, responsibility, honesty and social responsibility. However, this process still faces obstacles such as lack of teacher training, limited time in the curriculum, and high academic pressure. Therefore, collaboration between teachers, schools and parents is needed to create a learning environment that supports optimal character development.